The Analysis of Batch Processing Industry Characteristics and the Evaluation of MRP-II Suitability in This Context - Kang, Eng Thye (1996)
This project is initiated due to the major problems of MRP II installation fail in the world wide. Almost 80% failure are reported. However, these problems seem can not be solved easily. Besides that, my previous working experience in computer consulting firm and a multinational food manufacturing company in where my responsibility is to assist them selecting a process MRP-II has given me a great deal of valuable personnal experience and comment on the in the computer company software as well as the weaknesses of the user company operations. From the analysis result, the major cause is mainly the lack of understanding business environment in detail. Therefore, the aim of this dissertation is to explore the characteristics of different major batch industries and then evaluation is carried out on the MRP II suitability in this context. Finally, practical and real industries discussion are the main focus of this project for the need of the industries manager who intend to seek the MRP II software as well as the importance source for the vendors who need to understand the characteristics of each diferent batch industries.